A Comprehensive Review on Pharmaceutical Nanosuspension - as a Nanotechnology Tool for Solubility Enhancement - Naveen Taj, S.; Kavya, Y.; Dakshayani , M.; Lakshmi, K. Anitha (Challenges and Advances in Pharmaceutical Research Vol. 9, 2022)
Generally, low bioavailability is one of the major problems associated with poorly soluble drugs. This becomes more concerned problem in the case of drugs which are poorly soluble in both aqueous and non-aqueous media. To avoid all these problems, nanotechnology techniques have been introduced which is gaining much interest in improving the solubility of poorly soluble drugs. Use of nanosuspension emerged as a prominent, attractive and promising alternative for efficient delivery of such type of hydrophobic drugs. It is employed for the development of the novel drug formulations and they have emerged as a successful strategy for enhancing the solubility of the hydrophobic drugs due to their unique advantages. Bioavailability, stability and solubility of drugs are the factors that can be improved by the nanosuspension technology. Reducing the drug particle size into sub-micron size leads to a notable increase in the dissolution rate and they interact with the body at sub-cellular scales with the high degree of specificity, altering pharmacokinetics of drug and improving drug efficacy and safety. Nanosupension methods proved to achieve maximal therapeutic efficacy with minimal side effects and their unique features have enabled their usage in various dosage forms. They are commercially prepared by high pressure homogenization, media filling, and emulsification. Extensive efforts are being put into this field to extend their applications in the site specific drug delivery such as ocular, pulmonary and parenteral routes. This review article describes the preparation methods, characterization of nanosuspension including its benefits, marketed formulations and its pharmaceutical applications.